element
The power generation element with an uneven upper electrode and flexible intermediate layer increases power output by optimizing contact and peeling mechanisms, addressing the need for improved flexibility and power generation in existing elements.
Patent Information
- Application Number
- JP2021049141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-03-23
AI Technical Summary
Existing flexible power generation elements require improvements in power generation capacity.
A power generation element with an upper electrode having an uneven structure, a flexible intermediate layer, and a lower electrode that adheres to the intermediate layer, designed to generate an electric signal through contact or peeling, with the upper electrode fitting a convex structure when the intermediate layer is contacted or peeled off.
The design enhances the power generation capacity of flexible elements by increasing the contact area and improving the detachment process, leading to higher power output.
Smart Images

Figure 0007622495000001 
Figure 0007622495000002 
Figure 0007622495000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a device. [Background technology]
[0002] Technologies have been developed to improve the amount of power generated by flexible power generating elements (one example of an element). For example, a power generating element has been developed that has an upper electrode with a concave-convex structure, a flexible intermediate layer, and a lower electrode that is in close contact with the intermediate layer. Summary of the Invention [Problem to be solved by the invention]
[0003] However, flexible power generating elements are required to generate even more power.
[0004] The present invention has been made in view of the above, and has an object to provide a flexible element that can further improve the amount of power generation of the element. [Means for solving the problem]
[0005] In order to solve the above problems and achieve the object, the present invention provides an element having an upper electrode having a concave-convex structure, a flexible intermediate layer, and a lower electrode in close contact with the intermediate layer, and generating an electric signal by contact or peeling between the upper electrode and the intermediate layer, wherein the lower electrode has a shape that can be fitted into the concave-convex structure when the upper electrode and the intermediate layer come into contact with each other. When the upper electrode and the intermediate layer are peeled off, the upper electrode and the intermediate layer maintain a shape that can be fitted into the concave-convex structure. do. Effect of the Invention
[0006] According to the present invention, it is possible to further improve the amount of power generation by a flexible element. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a diagram for explaining an example of the configuration of a power generating element according to the present embodiment. [Diagram 2] FIG. 2 is a diagram for explaining an example of the operation of the lower electrode of the power generating element according to the present embodiment. [Diagram 3] FIG. 3 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. [Figure 4] FIG. 4 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. [Diagram 5] FIG. 5 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. [Figure 6] FIG. 6 is a diagram showing an example of a measuring device used to measure the amount of power generated by the power generating element according to the first embodiment. [Figure 7] FIG. 7 is a diagram showing an example of the material of the lower electrode used in measuring the amount of power generated by the power generating element according to the first embodiment. [Figure 8] FIG. 8 is a diagram showing an example of the measurement results of the power generation amount of the power generation element according to the first embodiment. [Figure 9] FIG. 9 is a diagram showing an example of the measurement results of the amount of power generated by the power generating element according to the second embodiment. [Figure 10] FIG. 10 is a diagram showing an example of the measurement results of the amount of power generated by the power generating element according to the third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the device will be described in detail with reference to the accompanying drawings.
[0009] FIG. 1 is a diagram for explaining an example of the configuration of a power generating element according to the present embodiment. FIG. 2 is a diagram for explaining an example of the operation of a lower electrode of the power generating element according to the present embodiment. As shown in FIG. 1(a), the power generating element 1 (an example of an element) according to the present embodiment has an upper cover 100, an upper electrode 101 (an example of a first electrode), an intermediate layer 102, a lower electrode 103 (an example of a second electrode), and a lower cover 104. Specifically, the power generating element 1 is an element in which the upper cover 100, the upper electrode 101, the intermediate layer 102, the lower electrode 103, and the lower cover 104 are laminated in this order, and may have other members as necessary.
[0010] The power generating element 1 is suitable for use in various sensors such as ultrasonic sensors, pressure sensors, tactile sensors, strain sensors, acceleration sensors, impact sensors, vibration sensors, pressure-sensitive sensors, electric field sensors, and sound pressure sensors, and is particularly suitable for wearable sensor applications since it does not require high voltage. Furthermore, as a piezoelectric film with excellent processability, the power generating element 1 is also suitable for use in headphones, speakers, microphones, underwater microphones, displays, fans, pumps, variable focus mirrors, ultrasonic transducers, piezoelectric transformers, sound insulation materials, soundproofing materials, actuators, keyboards, and the like. Furthermore, the power generating element 1 can be used in audio equipment, information processing devices, measuring instruments, medical equipment, and even vehicles and buildings, as well as vibration-damping materials (dampers) used in sports equipment such as skis and rackets, and in other fields.
[0011] Furthermore, the power generating element 1 is also suitable for the following applications. -Power generation from natural energy sources such as wave power, water power, and wind power -Embedded in shoes, clothing, floors and accessories, generating electricity from human footsteps -Embedded in car tires, etc., to generate electricity from vibrations generated by vehicle movement In addition, the power generating element 1 can be formed on a flexible substrate and used as a plate-shaped power generator, a secondary battery that is charged by applying voltage, or a new actuator (artificial muscle).
[0012] The upper cover 100 is a cover that covers the surface of the upper electrode 101 opposite to the surface that contacts the intermediate layer 102. The upper cover 100 is adhered to the upper electrode 101 by double-sided tape 105 or the like.
[0013] Examples of materials for the upper electrode 101 and the lower electrode 103 include metals, carbon-based conductive materials, conductive rubber compositions, conductive polymers, and oxides.
[0014] Examples of the metal include gold, silver, copper, aluminum, stainless steel, tantalum, nickel, and phosphor bronze.
[0015] Examples of the carbon-based conductive material include carbon nanotubes, carbon fibers, and graphite.
[0016] The conductive rubber composition may be, for example, a composition containing a conductive filler and rubber.
[0017] Examples of the conductive filler include carbon materials (e.g., ketjen black, acetylene black, graphite, carbon fiber, carbon fiber (CF), carbon nanofiber (CNF), carbon nanotube (CNT), graphene, etc.), metal fillers (gold, silver, platinum, copper, aluminum, nickel, etc.), conductive polymer materials (polythiophene, polyacetylene, polyaniline, polypyrrole, polyparaphenylene, and polyparaphenylenevinylene derivatives, or derivatives to which a dopant such as an anion or cation has been added), and ionic liquids. These may be used alone or in combination of two or more.
[0018] Examples of the rubber include silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, modified silicone, etc. These may be used alone or in combination of two or more.
[0019] Examples of the conductive polymer include polyethylenedioxythiophene (PEDOT), polypyrrole, and polyaniline.
[0020] Examples of the oxide include indium tin oxide (ITO), indium oxide-zinc oxide (IZO), and zinc oxide.
[0021] Examples of the form of the upper electrode 101 and the lower electrode 103 include a sheet, a film, a thin film, a woven fabric, a nonwoven fabric, a knitted fabric, a mesh, a sponge, etc. Note that the upper electrode 101 and the lower electrode 103 may be in the form of a nonwoven fabric formed by overlapping fibrous carbon materials.
[0022] The average thickness of the upper electrode 101 and the lower electrode 103 can be appropriately selected depending on the structure of the element, but from the viewpoint of electrical conductivity and flexibility, it is preferably 0.01 μm to 1 mm, and more preferably 0.1 μm to 500 μm. When the average thickness is 0.01 μm or more, the mechanical strength is appropriate and the electrical conductivity is improved. When the average thickness is 1 mm or less, the element is deformable and the power generation performance is good. In particular, a conductive rubber composition is preferable as the lower electrode 103.
[0023] The upper electrode 101 is an example of an upper electrode having an uneven structure. Specifically, the upper electrode 101 is an electrode having an uneven structure on the surface side that contacts the intermediate layer 102 described later. As a result, the upper electrode 101 has an uneven structure, and thus it is possible to improve the peelability between the upper electrode 101 and the intermediate layer 102. In this embodiment, the upper electrode 101 can be adhered to the upper cover 100 and the intermediate layer 102 by an adhesive layer 106 provided on the end portion of the upper electrode 101.
[0024] The intermediate layer 102 is an example of a flexible intermediate layer, and is sandwiched between the upper electrode 101 and the lower electrode 103. Specifically, the intermediate layer 102 is a power generator, and one surface of the intermediate layer 102 contacts (adheres) or peels off the uneven structure of the upper electrode 101, as shown in FIG. 1(b). In addition, as shown in FIG. 1(b), the lower electrode 103, which will be described later, is in close contact with the surface of the intermediate layer 102 opposite to the surface that contacts or peels off the uneven structure of the upper electrode 101. In addition, the intermediate layer 102 preferably has a thin film thickness in order to increase the amount of charge stored in the intermediate layer 102.
[0025] Preferably, the intermediate layer 102 satisfies at least one of the following conditions (1) and (2). Condition (1): When pressure is applied to the intermediate layer 102 from a direction perpendicular to the plane of the intermediate layer 102, the amount of deformation of the intermediate layer 102 on the upper electrode 101 (an example of a first electrode) side is different from the amount of deformation of the intermediate layer 102 on the lower electrode 103 (an example of a second electrode) side. Condition (2): The universal hardness (H1) of the intermediate layer 102 on the upper electrode 101 side when pressed through 10 μm is different from the universal hardness (H2) of the intermediate layer 102 on the lower electrode 103 side when pressed through 10 μm.
[0026] As described above, in the intermediate layer 102, by making the deformation amount or hardness different between the two surfaces, a large amount of power can be generated.
[0027] In this embodiment, the deformation amount is the maximum pressing depth of an indenter when the intermediate layer 102 is pressed under the following conditions. [Measurement conditions] Measuring instrument: Fischer ultra-microhardness tester WIN-HUD Indenter: Square pyramidal diamond indenter with facing angle of 136° Initial load: 0.02mN Maximum load: 1mN Load increase time from initial load to maximum load: 10 seconds The universal hardness is determined by the following method. [Measurement conditions] Measuring instrument: Fischer ultra-microhardness tester WIN-HUD Indenter: Square pyramidal diamond indenter with facing angle of 136° Indentation depth: 10 μm Initial load: 0.02mN Maximum load: 100mN Load increase time from initial load to maximum load: 50 seconds
[0028] The ratio (H1 / H2) of the universal hardness (H1) to the universal hardness (H2) is preferably 1.01 or more, more preferably 1.07 or more, and particularly preferably 1.13 or more. There is no particular upper limit to the ratio (H1 / H2), and it is appropriately selected depending on, for example, the degree of flexibility required in the usage state and the load in the usage state, but it is preferably 1.70 or less. Here, H1 is the universal hardness of the relatively hard surface, and H2 is the universal hardness of the relatively soft surface.
[0029] The material of the intermediate layer 102 is not particularly limited and can be appropriately selected depending on the purpose. Examples of the material include rubber and rubber compositions.
[0030] Examples of the rubber include silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, modified silicone, etc. These may be used alone or in combination of two or more. Among these, silicone rubber is preferred.
[0031] The silicone rubber is not particularly limited as long as it is a rubber having a siloxane bond, and can be appropriately selected according to the purpose. Examples of the silicone rubber include dimethyl silicone rubber, methylphenyl silicone rubber, fluorosilicone rubber, and modified silicone rubber (e.g., acrylic modified, alkyd modified, ester modified, and epoxy modified). These may be used alone or in combination of two or more.
[0032] The rubber composition may be, for example, a composition containing a filler and the rubber, etc. Among these, a silicone rubber composition containing the silicone rubber is preferred because it has high power generation performance.
[0033] Examples of the filler include organic fillers, inorganic fillers, and organic-inorganic composite fillers. The organic filler is not particularly limited as long as it is an organic compound, and can be appropriately selected according to the purpose. Examples of the organic filler include acrylic fine particles, polystyrene fine particles, melamine fine particles, fluororesin fine particles such as polytetrafluoroethylene, silicone powder (silicone resin powder, silicone rubber powder, silicone composite powder), rubber powder, wood powder, pulp, and starch. The inorganic filler is not particularly limited as long as it is an inorganic compound, and can be appropriately selected according to the purpose.
[0034] Examples of the inorganic filler include oxides, hydroxides, carbonates, sulfates, silicates, nitrides, carbons, metals, and other compounds.
[0035] Examples of the oxide include silica, diatomaceous earth, alumina, zinc oxide, titanium oxide, iron oxide, and magnesium oxide.
[0036] Examples of the hydroxide include aluminum hydroxide, calcium hydroxide, and magnesium hydroxide.
[0037] Examples of the carbonate include calcium carbonate, magnesium carbonate, barium carbonate, and hydrotalcite.
[0038] Examples of the sulfate include aluminum sulfate, calcium sulfate, and barium sulfate.
[0039] Examples of the silicate include calcium silicate (wollastonite, xonotlite), zircon silicate, kaolin, talc, mica, zeolite, perlite, bentonite, montmoronite, sericite, activated clay, glass, and hollow glass beads.
[0040] Examples of the nitride include aluminum nitride, silicon nitride, and boron nitride.
[0041] Examples of the carbons include ketjen black, acetylene black, graphite, carbon fiber, carbon nanofiber, carbon nanotube, fullerene (including derivatives), and graphene.
[0042] Examples of the metal include gold, silver, platinum, copper, iron, aluminum, and nickel.
[0043] Examples of the other compounds include potassium titanate, barium titanate, strontium titanate, lead zirconate titanate, silicon carbide, molybdenum sulfide, etc. The inorganic filler may be surface-treated.
[0044] The organic-inorganic composite filler is not particularly limited as long as it is a compound in which an organic compound and an inorganic compound are combined at the molecular level.
[0045] Examples of the organic-inorganic composite filler include silica-acrylic composite fine particles and silsesquioxane.
[0046] The average particle size of the filler is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.01 μm to 30 μm, and more preferably 0.1 μm to 10 μm. When the average particle size is 0.01 μm or more, the power generation performance may be improved. When the average particle size is 30 μm or less, the intermediate layer is deformable, and the power generation performance can be increased.
[0047] The average particle size can be measured by a known method using a known particle size distribution measuring device, such as Microtrac HRA (manufactured by Nikkiso Co., Ltd.).
[0048] The content of the filler is preferably 0.1 to 100 parts by mass, more preferably 1 to 50 parts by mass, based on 100 parts by mass of rubber. When the content is 0.1 parts by mass or more, the power generation performance may be improved. When the content is 100 parts by mass or less, the intermediate layer is deformable, and the power generation performance can be improved.
[0049] The other components are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include additives, etc. The content of the other components can be appropriately selected to the extent that the purpose of the present embodiment is not impaired.
[0050] Examples of the additives include crosslinking agents, reaction control agents, fillers, reinforcing materials, antioxidants, conductivity control agents, colorants, plasticizers, processing aids, flame retardants, ultraviolet absorbers, tackifiers, and thixotropy-imparting agents.
[0051] There are no particular limitations on the method for preparing the material constituting the mid layer 102, and it may be appropriately selected depending on the purpose. For example, the rubber composition may be prepared by mixing the rubber and the filler, and further the other components as necessary, and kneading and dispersing them.
[0052] The method for forming the intermediate layer 102 is not particularly limited and may be appropriately selected depending on the purpose. For example, a method for forming a thin film of the rubber or the rubber composition may include a method in which the rubber or the rubber composition is applied onto a substrate by blade coating, die coating, dip coating, spin coating, or the like, and then cured by heat, electron beams, moisture in the air, or the like.
[0053] The average thickness of the intermediate layer 102 is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of deformation followability, it is preferably 0.01 μm to 10 mm, more preferably 0.1 μm to 100 μm. Furthermore, when the average thickness is within the preferred range, film formability can be ensured and deformation is not hindered, so that good power generation can be performed, but a smaller film thickness is preferable for improving the amount of power generation.
[0054] The intermediate layer 102 is preferably insulating. The insulating property is preferably such that the intermediate layer 102 has a volume resistivity of 108 Ωcm or more, and more preferably has a volume resistivity of 1010 Ωcm or more. The intermediate layer 102 may have a multi-layer structure.
[0055] The intermediate layer 102 may undergo a surface modification or passivation treatment.
[0056] [Surface modification treatment] The surface modification treatment may be either a dry treatment or a wet treatment, but is more preferred to be a dry treatment. Examples of dry treatments include plasma treatment, corona discharge treatment, electron beam irradiation treatment, ultraviolet irradiation treatment, ozone treatment, and radiation (X-rays, α-rays, β-rays, γ-rays, and neutron beam) irradiation treatment. Among these treatments, plasma treatment, corona discharge treatment, and electron beam irradiation treatment are preferred in terms of processing speed, but are not limited to these as long as they have a certain degree of irradiation energy and can modify the material. The surface modification means chemically changing the surface of the intermediate layer.
[0057] [Plasma treatment] In the case of plasma treatment, the plasma generating device may be, for example, a parallel plate type, a capacitively coupled type, an inductively coupled type, or an atmospheric pressure plasma device. From the viewpoint of durability, reduced pressure plasma treatment is preferred.
[0058] The reaction pressure in the plasma treatment is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.05 Pa to 100 Pa, and more preferably 1 Pa to 20 Pa.
[0059] The reaction atmosphere in the plasma treatment is not particularly limited and can be appropriately selected according to the purpose. For example, inert gas, rare gas, oxygen, and other gases are effective, but argon is preferable in terms of the durability of the effect. In addition, it is preferable to set the oxygen partial pressure to 5,000 ppm or less. If the oxygen partial pressure in the reaction atmosphere is 5,000 ppm or less, the generation of ozone can be suppressed, and the use of an ozone treatment device can be avoided.
[0060] The amount of irradiation power in the plasma treatment is determined by (output x irradiation time). The amount of irradiation power is preferably 5 Wh to 200 Wh, and more preferably 10 Wh to 50 Wh. When the amount of irradiation power is within the preferred range, the intermediate layer 102 can be endowed with a power generating function, and durability is not reduced due to excessive irradiation.
[0061] [Corona discharge treatment] The applied energy (accumulated energy) in corona discharge treatment is 6J / cm2 to 300J / cm 2 is preferred, and 12 J / cm 2 ~60J / cm 2 When the applied energy is within the preferred range, the intermediate layer 102 can be endowed with a power generating function, and durability is not reduced due to excessive irradiation.
[0062] [Electron beam irradiation treatment] The dose in the electron beam irradiation treatment is preferably 1 kGy or more, and more preferably 300 kGy to 10 MGy. When the dose is within the preferred range, the intermediate layer 102 can be endowed with a power generating function, and durability is not reduced due to excessive irradiation. The reaction atmosphere in the electron beam irradiation treatment is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the reaction atmosphere is filled with an inert gas such as argon, neon, helium, nitrogen, etc., and the oxygen partial pressure is 5,000 ppm or less. When the oxygen partial pressure in the reaction atmosphere is 5,000 ppm or less, ozone generation can be suppressed, and the use of an ozone treatment device can be avoided.
[0063] [Ultraviolet light irradiation treatment] The ultraviolet light in the ultraviolet irradiation treatment preferably has a wavelength of 365 nm or less and 200 nm or more, and more preferably has a wavelength of 320 nm or less and 240 nm or more. The integrated light amount in the ultraviolet irradiation treatment is 5 J / cm. 2 ~500J / cm 2 is preferred, and 50 J / cm 2 ~400J / cm 2 is more preferable. When the integrated light amount is within the preferable range, the intermediate layer 102 can be endowed with a power generating function, and durability is not reduced due to excessive irradiation. The reaction atmosphere in the ultraviolet irradiation treatment is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the atmosphere is filled with an inert gas such as argon, neon, helium, nitrogen, etc., and the oxygen partial pressure is 5,000 ppm or less. When the oxygen partial pressure in the reaction atmosphere is 5,000 ppm or less, ozone generation can be suppressed, and the use of an ozone treatment device can be avoided.
[0064] In the prior art, it has been proposed to form active groups by excitation or oxidation using plasma treatment, corona discharge treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, etc., to increase interlayer adhesion. However, this technique is limited to application between layers, and it is known that application to the outermost surface is undesirable because it reduces releasability. In addition, the reaction is carried out under oxygen-rich conditions to effectively introduce reactive active groups (hydroxyl groups). Therefore, such prior art is essentially different from the surface modification treatment of the present embodiment.
[0065] The surface modification treatment of this embodiment is a treatment in a reaction environment with little oxygen and reduced pressure (e.g., plasma treatment), which promotes re-crosslinking and bonding of the surface, and it is thought that, for example, durability is improved due to "an increase in Si-O bonds with high bond energy", and further releasability is improved due to "densification due to increased crosslink density" (note that, although some active groups are formed in this embodiment as well, the active groups are inactivated by a coupling agent or air drying treatment described below).
[0066] [Inactivation treatment] The surface of the intermediate layer 102 may be appropriately inactivated using various materials. The inactivation treatment is not particularly limited as long as it is a treatment that inactivates the surface of the intermediate layer 102, and may be appropriately selected depending on the purpose. For example, a treatment that applies an inactivating agent to the surface of the intermediate layer 102 may be mentioned. Inactivation means changing the surface of the intermediate layer 102 to a property that is less likely to cause chemical reactions. This change is obtained by reacting active groups (e.g., -OH, etc.) generated by excitation or oxidation by plasma treatment, corona discharge treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, etc., with an inactivating agent to reduce the activity of the surface of the intermediate layer 102.
[0067] Examples of the deactivating agent include an amorphous resin and a coupling agent.
[0068] The amorphous resin may, for example, be a resin having a perfluoropolyether structure in the main chain.
[0069] Examples of the coupling agent include metal alkoxides, solutions containing metal alkoxides, etc. Examples of the metal alkoxides include compounds represented by the following formula (1), partial hydrolysis polycondensates thereof having a degree of polymerization of about 2 to 10, and mixtures thereof. R 1 (4-n) Si(OR 2 ) n (1) In the above formula (1), R1 and R2 each independently represent a linear or branched alkyl group having 1 to 10 carbon atoms, an alkyl polyether chain, or an aryl group. n represents an integer of 2 to 4.
[0070] Specific examples of the compound represented by the above formula (1) include dimethyldimethoxysilane, diethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, etc. Tetraethoxysilane is particularly preferred in terms of durability.
[0071] In the above formula (1), R1 may be a fluoroalkyl group, or may be a fluoroalkyl acrylate or ether perfluoropolyether bonded via oxygen. In terms of flexibility and durability, a perfluoropolyether group is particularly preferred.
[0072] Further, examples of the metal alkoxide include vinyl silanes [e.g., vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, etc.], acryl silanes [e.g., γ-methacryloxypropyltrimethoxysilane, etc.], epoxy silanes [e.g., β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, etc.], amino silanes [N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, etc.], and the like.
[0073] In addition, the metal alkoxide may contain, as the metal atom, Ti, Sn, Al, or Zr, other than Si, either alone or in combination of two or more of them.
[0074] The inactivation treatment can be carried out, for example, by impregnating the surface of the intermediate layer precursor, such as rubber, with the inactivator by coating or dipping, etc., after the surface modification treatment is performed on the intermediate layer precursor. Inactivation may also be carried out by methods such as plasma CVD, PVD, sputtering, vacuum deposition, and combustion chemical vapor deposition.
[0075] When silicone rubber is used as the intermediate layer precursor, the intermediate layer precursor may be deactivated by being left to stand in air and air-dried after the surface modification treatment.
[0076] It is preferable that the oxygen concentration profile in the thickness direction of the intermediate layer 102 has a maximum value.
[0077] It is preferable that the carbon concentration profile in the thickness direction of the intermediate layer 102 has a minimum value.
[0078] In the intermediate layer 102, it is more preferable that the position where the oxygen concentration profile shows a maximum value coincides with the position where the carbon concentration profile shows a minimum value.
[0079] The oxygen concentration profile and the carbon concentration profile can be determined by X-ray photoelectron spectroscopy (XPS). Examples of the measurement method include the following methods. [Measurement method] Measurement equipment: Ulvac-PHI QuanteraSXM, manufactured by Ulvac-Phi Inc. Measurement light source: Al(mono) Measurement output: 100μmφ, 25.1W Measurement area: 500μm x 300μm Pass energy: 55 eV (narrow scan) Energy step: 0.1 eV (narrow scan) Relative sensitivity coefficient: Use the relative sensitivity coefficient of PHI Sputtering source: C60 cluster ions Ion Gun Output: 10 kV, 10 nA Raster Control:(X=0.5,Y=2.0)mm Sputter rate: 0.9 nm / min (SiO2 equivalent)
[0080] In XPS, the concentration ratio and bonding state of atoms in the object being measured can be determined by capturing electrons that are emitted due to the photoelectron effect.
[0081] The silicone rubber has a siloxane bond and is mainly composed of Si, O, and C. Therefore, when silicone rubber is used as the material of the intermediate layer, the XPS wide scan spectrum is measured, and the concentration ratio of each atom present from the surface layer to the inside in the depth direction can be obtained from the relative peak intensity ratio of each element.
[0082] Furthermore, in the case of silicone rubber, the elements bonded to silicon and their bonding state can be determined by measuring the energy of electrons ejected from the Si 2p orbital. The chemical bonding state can be determined by peak separation from the narrow scan spectrum of the Si 2p orbital, which indicates the bonding state of Si.
[0083] It is generally known that the amount of peak shift depends on the bonding state. In the case of silicone rubber that has been subjected to the above-mentioned surface treatment and / or passivation treatment, a peak shift to the higher energy side is observed in the Si2p orbital, which indicates that the number of oxygen atoms bonded to Si has increased.
[0084] When a surface treatment such as a surface modification treatment or a passivation treatment is performed on the surface of the intermediate layer 102 on the upper electrode 101 side, the surface of the intermediate layer 102 on the upper electrode 101 side becomes harder than the surface of the intermediate layer 102 on the lower electrode 103 side. Therefore, the universal hardness H1 of the surface of the intermediate layer 102 on the upper electrode 101 side becomes higher than the universal hardness H2 of the surface of the intermediate layer 102 on the lower electrode 103 side. As a result, when the same deformation applying force F is applied to the upper electrode 101 side and the lower electrode 103 side, the degree of deformation of the upper electrode 101 side of the intermediate layer 102 becomes smaller than that of the lower electrode 103 side, and the uneven structure of the upper electrode 101 can be made to bite more into the lower electrode 103. As a result, the amount of power generated by the power generating element 1 can be increased.
[0085] The intermediate layer 102 does not need to have an initial surface potential when left to stand. The initial surface potential when left to stand can be measured under the following measurement conditions. Here, "not having an initial surface potential" means that the initial surface potential is ±10 V or less when measured under the following measurement conditions. [Measurement conditions] Pretreatment: After leaving the sample in an atmosphere of 30°C and 40% relative humidity for 24 hours, static electricity was removed for 60 seconds (using Keyence's SJ-F300). Equipment:Treck Model344 Measurement probe: 6000B-7C Measurement distance: 2mm Measurement spot diameter: diameter (Φ) 10 mm In this respect, the power generating element 1 according to this embodiment is considered to have a different power generation principle from the techniques described in JP 2009-253050 A, JP 2014-027756 A, JP 54-14696 A, etc. Without being bound by any theory, it is considered that the power generating element 1 (one example of an element) according to this embodiment generates power by generating charges due to peeling between the upper electrode 101 and the intermediate layer 102, and then storing the charges in the intermediate layer 102 at that time, which causes electrostatic induction to move the charges.
[0086] The lower electrode 103 (an example of a second electrode) is an example of a lower electrode that is in close contact with the intermediate layer 102. The power generating element 1 is an element that generates an electric signal by contact or peeling between the upper electrode 101 and the intermediate layer 102. As shown in FIG. 1(b), the lower electrode 103 has a shape that can be fitted into the uneven structure of the upper electrode 101 when the upper electrode 101 and the intermediate layer 102 come into contact with each other. This allows the upper electrode 101 to sufficiently bite into the power generating body as the intermediate layer 102 when the upper electrode 101 and the intermediate layer 102 come into contact with each other (i.e., when a load is applied from the upper electrode 101 side to the lower electrode 103 side) as shown in FIG. 2, and the contact area between the upper electrode 101 and the intermediate layer 102 can be increased. As a result, the amount of power generated by the power generating element 1 can be further improved. It is preferable that the lower electrode 103 maintains a shape that can be fitted into the uneven structure of the upper electrode 101 when the upper electrode 101 and the intermediate layer 102 are peeled off.
[0087] The power generating element 1 (an example of an element) of this embodiment preferably has a space between the intermediate layer 102 and at least one of the upper electrode 101 (an example of a first electrode) and the lower electrode 103 (an example of a second electrode). This can increase the amount of power generation.
[0088] The method for providing the space is not particularly limited and can be appropriately selected depending on the purpose. For example, a method may be used in which a spacer is disposed between the intermediate layer 102 and at least one of the upper electrode 101 (an example of a first electrode) and the lower electrode 103 (an example of a second electrode).
[0089] The spacer is not particularly limited in terms of material, form, shape, size, etc., and may be appropriately selected depending on the purpose. Examples of the material of the spacer include polymer materials, rubber, metals, conductive polymer materials, conductive rubber compositions, etc.
[0090] Examples of the polymeric material include polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polyimide resin, fluororesin, acrylic resin, etc. Examples of the rubber include silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, modified silicone, etc.
[0091] Examples of the metal include gold, silver, copper, aluminum, stainless steel, tantalum, nickel, and phosphorus bronze. Examples of the conductive polymer material include polythiophene, polyacetylene, and polyaniline. Examples of the conductive rubber composition include a composition containing a conductive filler and rubber. Examples of the conductive filler include carbon materials (e.g., ketjen black, acetylene black, graphite, carbon fiber, carbon fiber, carbon nanofiber, carbon nanotube, graphene, etc.), metals (e.g., gold, silver, platinum, copper, iron, aluminum, nickel, etc.), conductive polymer materials (e.g., derivatives of any of polythiophene, polyacetylene, polyaniline, polypyrrole, polyparaphenylene, and polyparaphenylenevinylene, or derivatives of these derivatives to which a dopant such as an anion or cation has been added), and ionic liquids.
[0092] Examples of the rubber include silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, and modified silicone.
[0093] Examples of the form of the spacer include a sheet, a film, a woven fabric, a nonwoven fabric, a mesh, and a sponge.
[0094] The spacer arrangement pattern may be a dot, a line, a grid, or the like.
[0095] The shape, size, thickness and installation location of the spacer can be appropriately selected depending on the structure of the element.
[0096] The power generating element 1 (one example of an element) of this embodiment may have, for example, upper and lower cover members as other members. The material, shape, size, thickness, and structure of the upper and lower cover members are not particularly limited and may be appropriately selected depending on the purpose.
[0097] Examples of the material for the cover include polymer materials and rubber.
[0098] Examples of the polymeric material include polyethylene, polypropylene, polyethylene terephthalate, polyvinyl chloride, polyimide resin, fluororesin, and acrylic resin.
[0099] Examples of the rubber include silicone rubber, modified silicone rubber, acrylic rubber, chloroprene rubber, polysulfide rubber, urethane rubber, butyl rubber, fluorosilicone rubber, natural rubber, ethylene-propylene rubber, nitrile rubber, fluororubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, chlorosulfonated polyethylene rubber, polyisobutylene, etc. A rubber material is preferable for the lower cover.
[0100] The lower cover 104 is provided on the surface of the lower electrode 103 opposite to the surface that is in close contact with the intermediate layer 102. In this case, the lower cover 104 is shaped so that it can fit into the uneven structure of the upper electrode 101 together with the lower electrode 103 when the upper electrode 101 and the intermediate layer 102 come into contact with each other. This allows the upper electrode 101 to sufficiently bite into the power generating body serving as the intermediate layer 102 when the upper electrode 101 and the intermediate layer 102 come into contact with each other, thereby increasing the contact area between the upper electrode 101 and the intermediate layer 102. As a result, the amount of power generated by the power generating element 1 can be further improved.
[0101] Fig. 3 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. In Fig. 3, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the material used for the lower electrode 103. Next, an example of the difference in the amount of power generated by the power generating element 1 due to differences in the material used for the lower electrode 103 will be described with reference to Fig. 3.
[0102] 3, the amount of power generated by the power generating element 1 is greater when the lower electrode 103 is made of conductive silicone rubber, which is easily deformed into a shape that can fit into the concave-convex structure of the upper electrode 101, than when the lower electrode 103 is made of metal foil (e.g., aluminum foil) or conductive polymer (film thickness: 4 μm), which is difficult to deform into a shape that can fit into the concave-convex structure of the upper electrode 101. Therefore, it is preferable to use a material (e.g., conductive silicone rubber) that is easily deformed into a shape that can fit into the concave-convex structure of the upper electrode 101 for the lower electrode 103. This can further improve the amount of power generated by the power generating element 1.
[0103] Fig. 4 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. In Fig. 4, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the hardness of the lower electrode 103 (conductive silicone rubber with a film thickness of 10 µm). Next, an example of the difference in the amount of power generated by the power generating element 1 due to differences in the hardness of the lower electrode 103 will be described with reference to Fig. 4.
[0104] 4, as the hardness of the lower electrode 103 decreases and it becomes easier to fit with the concave-convex structure of the upper electrode 101, the power generation amount of the power generating element 1 increases. Therefore, it is preferable to use, for the lower electrode 103, a lower electrode having a hardness that allows it to easily deform into a shape that can fit with the concave-convex structure of the upper electrode 101. This can further improve the power generation amount of the power generating element 1.
[0105] Fig. 5 is a diagram showing an example of the amount of power generated by the power generating element according to the present embodiment. In Fig. 5, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the elastic modulus (elastic power) of the lower electrode 103. Next, an example of a difference in the amount of power generated by the power generating element 1 due to differences in the elastic modulus of the lower electrode 103 will be described with reference to Fig. 5.
[0106] 5, as the elastic modulus of the lower electrode 103 decreases and the contact area between the upper electrode 101 and the intermediate layer 102 increases (in other words, as it becomes easier to fit with the concave-convex structure of the upper electrode 101), the amount of power generated by the power generating element 1 increases. Therefore, it is preferable to use, for the lower electrode 103, a lower electrode having an elastic modulus that easily deforms into a shape that can fit with the concave-convex structure of the upper electrode 101. This can further improve the amount of power generated by the power generating element 1.
[0107] Thus, according to the power generating element 1 of this embodiment, when the upper electrode 101 and the intermediate layer 102 come into contact with each other, the upper electrode 101 can sufficiently bite into the power generating body serving as the intermediate layer 102, thereby increasing the contact area between the upper electrode 101 and the intermediate layer 102. As a result, the amount of power generated by the power generating element 1 can be further improved.
[0108] (First embodiment) This embodiment is an example in which the material of the lower electrode 103 is changed and the amount of power generated by the power generating element 1 is measured.
[0109] FIG. 6 is a diagram showing an example of a measuring device used to measure the amount of power generated by the power generating element according to the first embodiment. In this embodiment, the measuring device 600 has an oscilloscope 601 (for example, WAVEACE1001, Teledyne Japan Co., Ltd.) capable of measuring the voltage across the resistor R (10 MΩ) connected to the upper electrode 101 and the lower electrode 103, as shown in FIG. 6. Here, a cloth electrode (for example, Sui-10-70, manufactured by Seiren Co., Ltd.) is used for the upper electrode 101. Silicone rubber (KE-106, manufactured by Shin-Etsu Chemical Co., Ltd.) is used for the intermediate layer 102. Specifically, the intermediate layer 102 may be formed by applying silicone rubber to the lower electrode 103 by blade coating, curing the silicone rubber in an oven at 120° C. for 5 minutes to form a film with a thickness of 15 μm, and then performing an electron beam irradiation process (EE-L-RC01, manufactured by Hamamatsu Photonics K.K.). The lower electrode 103 is fixed on the stage of the measuring device 600 and is connected to GND. The hardness and elastic modulus of the lower electrode 103 are measured using a microhardness tester (FISHER SCOPE HM2000 manufactured by Fisher Instruments Inc., indenter: Vickers indenter).
[0110] 6, in this embodiment, the upper electrode 101 is movable in the vertical direction, and the upper electrode 101 can be brought into contact with and peeled off from the intermediate layer 102. The measuring device 600 converts the waveform of the voltage measured by the oscilloscope 601 when the upper electrode 101 comes into contact with and peels off from the intermediate layer 102 into an amount of transferred charge, and calculates the total value as the amount of power generation. For example, the measuring device 600 calculates the amount of power generation at the 50th contact and peeling between the upper electrode 101 and the intermediate layer 102.
[0111] Fig. 7 is a diagram showing an example of the material of the lower electrode used in measuring the amount of power generated by the power generating element according to the first example. Fig. 8 is a diagram showing an example of the measurement results of the amount of power generated by the power generating element according to the first example. In Fig. 8, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the material of the lower electrode 103. Next, an example of the measurement results of the amount of power generated by the power generating element 1 using the measuring device 600 shown in Fig. 6 will be described with reference to Figs. 7 and 8.
[0112] 7 and 8, the power generation amount of the power generating element 1 is the largest when conductive silicone rubber is used as the lower electrode 103. This is believed to be because, as the hardness of the lower electrode 103 decreases, the lower electrode 103 also becomes more easily deformed when the upper electrode 101 and the intermediate layer 102 come into contact with each other, which makes it easier to form an interlocking shape between the upper electrode 101 and the intermediate layer 102 and increases the contact area between the upper electrode 101 and the intermediate layer 102.
[0113] (Second Example) This example is an example in which the hardness of the lower electrode 103 (for example, conductive silicone rubber with a film thickness of 100 μm) is changed and the amount of power generated by the power generating element 1 is measured. In this example, as in the first example, the amount of power generated by the power generating element 1 is measured using the measuring device 600 shown in FIG.
[0114] Fig. 9 is a diagram showing an example of the measurement results of the amount of power generated by the power generating element according to the second example. In Fig. 9, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the hardness of the lower electrode 103. As shown in Fig. 9, the result shows that the amount of power generated by the power generating element 1 increases as the hardness of the lower electrode 103 decreases. This is believed to be because a lower hardness of the lower electrode 103 makes it easier for the lower electrode 103 to deform when the upper electrode 101 and the intermediate layer 102 come into contact with each other, making it easier to form an interlocking shape between the upper electrode 101 and the intermediate layer 102, and increasing the contact area between the upper electrode 101 and the intermediate layer 102.
[0115] (Third Example) This example is an example in which the amount of power generated by the power generating element 1 was measured by changing the elastic modulus (elastic power) of the lower electrode 103 (for example, conductive silicone rubber with a film thickness of 100 μm). In this example, as in the first example, the amount of power generated by the power generating element 1 was measured using the measuring device 600 shown in FIG.
[0116] FIG. 10 is a diagram showing an example of the measurement result of the amount of power generated by the power generating element according to the third embodiment. In FIG. 10, the vertical axis represents the amount of power generated by the power generating element 1, and the horizontal axis represents the elastic power of the lower electrode 103. As shown in FIG. 10, the result was obtained in which the amount of power generated by the power generating element 1 increases as the elastic power of the lower electrode 103 decreases. The amount of power generated by the power generating element 1 tends to saturate in due course as the contact area between the upper electrode 101 and the intermediate layer 102 increases with the number of contacts and peels. In this case, it is considered that the smaller the elastic power of the lower electrode 103, the easier it is to maintain the deformation of the lower electrode formed when the upper electrode 101 and the intermediate layer 102 come into contact with each other, and the easier it is to stabilize the contact area between the upper electrode 101 and the intermediate layer 102. Therefore, it is considered that the smaller the elastic power of the lower electrode 103, the more the amount of power generated by the power generating element 1 is improved. [Explanation of symbols]
[0117] 1 Power generating element 100 Top cover 101 Upper electrode 102 Middle Class 103 Lower electrode 104 Lower cover 105 Double-sided tape 106 Adhesive layer [Prior art documents] [Patent documents]
[0118] [Patent Document 1] JP 2011-172366 A [Patent Document 2] Patent No. 5945102
Claims
1. An element having an upper electrode having a concave-convex structure, a flexible intermediate layer, and a lower electrode in close contact with the intermediate layer, the element generating an electric signal by contact or peeling between the upper electrode and the intermediate layer, An element in which the lower electrode takes on a shape that can fit with the uneven structure when the upper electrode and the intermediate layer come into contact, and maintains a shape that can fit with the uneven structure when the upper electrode and the intermediate layer are peeled off.
2. An element comprising an upper electrode having a concave-convex structure, a flexible intermediate layer, a lower electrode in close contact with the intermediate layer, and a lower cover provided on a surface of the lower electrode opposite to a surface in close contact with the intermediate layer, the element generating an electric signal by contact or peeling between the upper electrode and the intermediate layer, the lower electrode and the lower cover have shapes that can be fitted into the concave-convex structure when the upper electrode and the intermediate layer come into contact with each other; The lower electrode maintains a shape that allows it to fit into the concave-convex structure when the upper electrode and the intermediate layer are peeled off.
Citation Information
Patent Citations
Manufacture of square pillar from small-diameter wood
JP1984045102A
Power generation mat
JP2011172366A
Power generator
JP2017108596A
Triboelectric Generators and Sensors
US20140338458A1